Paraspinal Muscle Response to Electrical Vestibular Stimulation - ARDIC, F. N; LATT, L. D; REDFERN, M. S (Acta oto-laryngologica, 2000)
Galvanic (electrical) vestibular stimulation (GVS) has been used to study the role of the vestibular system in postural control by inducing postural sway in standing subjects. The purpose of this study was to determine the timing and pattern of activation in the paraspinal muscles in response to GVS and to compare these responses with those in the muscles of the lower leg. Binaural-bipolar GVS was applied to the skin overlying the mastoid processes of 10 subjects while they stood on a force plate with their eyes closed. The stimulus consisted of a 0.6 mA 5-pulse sequence. Each pulse lasted for 2 s, followed by 4 s of rest. The centre of pressure (COP) vs. time for each trial was calculated from the reaction forces and moments. Surface electromyographic (EMG) signals from the paraspinal and gastrocnemius muscles were recorded bilaterally. The EMG signals were rectified and integrated (iEMG). The iEMG from the muscles on the cathodal side of the body were then subtracted from the iEMG of the anodal side muscles, to yield a differential EMG (dEMG). Both the paraspinal and gastrocnemius muscles became activated in response to the stimulus. The pattern of activation was consistent with the changes observed in the centre of pressure. The primary response in both muscles acted to move the body toward the anode. This primary response began at 74 +/- 20 ms in the paraspinal muscles and at 118 +/- 18 ms in the gastrocnemius. A second component of the response began at 232 +/- 27 ms in the paraspinal muscles and 262 +/- 54 ms in the gastrocnemius muscles. This second phase of the response was opposite in direction to the primary response and was responsible for decelerating the body and maintaining the deviated position of the centre of mass over the base of support. Following the termination of the stimulus, the opposite pattern of muscle activation in both the paraspinal and the gastrocnemius muscles was observed. The results of this study suggest that the paraspinal muscles may play a significant role in the frontal plane response to vestibular stimulation during stance in humans.